Isolation of Giant Viruses of Acanthamoeba castellanii. Issue 5 (25th May 2022) - Machado, Talita Bastos; de Aquino, Isabella Luiza Martins; Abrahão, Jônatas Santos
Abstract: This article describes a practical method for prospecting and isolating giant viruses based on direct inoculation of environmental samples into amoeba cultures of Acanthamoeba castellanii . The giant viruses that infect amoebas have already been isolated from various environmental samples in several countries worldwide, including in extreme environments. Here we describe the methodologic procedures regarding the prospecting of giant viruses in A. castellanii, including the preparation of environmental samples, the culture of amoebas, and the observation of cytopathic effects that can indicate the presence and potential isolation of giant viruses. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Sample collection Support Protocol : Propagation of Acanthamoeba castellanii Basic Protocol 2 : Prospecting of giant viruses in environmental samples by cytopathic effect analysis